Impact of Preceding El Niño and the Indian Ocean Dipole on the Southern China Precipitation in Early Summer - Yan Li; Yafei Wang; Lin Mu; Qingyuan Wang; Jun Song; Guosong Wang (Advances in Meteorology)
Delayed impacts of El Niño and the Indian Ocean Dipole in positive phase (P-IOD) on the South China early monsoon were investigated by observations and simulations. The most significant correlation between IOD index (IODI) and NINO3 appeared in boreal autumn. A new index (IODN3) related to the intensity of El Niño and IOD was created. Three indexes in boreal autumn were positively well correlated with the rainfall over the Yangtze River and its southern area (rain-YRBS) in next June. The most significant correlation appeared between IODN3 and rain-YRBS. Positive rain-YRBS anomalies in June tend to occur after P-IOD or El Niño solely matured in previous boreal autumn. However, when both events matured in boreal autumn, rain-YRBS anomalies tended to be more enhanced, which suggests that a delayed combined influence of both events on rain-YRBS in June was larger than that of either event alone. There was a low level anticyclonic circulation around the Philippines (PSAC) that developed in boreal autumn and was maintained until the following June when the single event occurred. However, a much stronger PSAC tended to occur when both events matured. The stronger PSAC could transport more water vapor to YRBS and cause more rainfall there in June.